Funkcjonowanie wybranych rynków oligopolistycznych w Polsce w aspekcie działań Urzędu Ochrony Konkurencji i Konsumentów - Bochan, Radosław (Gospodarka w Praktyce i Teorii, 2012)
The profile of some was introduced in the present article, discordant with the right workings, chosen enterprises act on Polish oligopolic markets the which became detects thanks to supervisory workings Office of Fair Trading (UOKiK). The cartel collusions which have the place on various, Polish oligopolic markets predominate the various kind in the objective catalogue of described delicts. Illegal agreements can concern the inflated price not only, but also the different elements of marketing mix tj. the product, distribution, if the promotion. The consumer from these cases, on the wasted position stands up in every one or /and competitive enterprises which are not the participants of this agreement. That is why proper workings subjects entitled to monitors, finds and limits practician monopolistic he is the key element of the existence of the free market. Last years show that the workings of UOKiK reconcile in the businesses of the dishonest businessmen who in the discordant way with the right desire to maximalize of one’s profits more and more painfully.